The Pachycondyla Apicalis metaheuristic algorithm for parameters identification of chaotic electrical system. Issue 5 (3rd September 2018) - Maamri, F.; Bououden, S.; Chadli, M.; Boulkaibet, I.
Abstract: In this work, the Pachycondyla Apicalis metaheuristic algorithm (API) is used to identify and optimize control parameters for piezoelectric oscillator that exhibits frequency hysteresis behavior under strong excitation when asymmetric period which the bifurcation and chaotic behavior of higher harmonics appear by minimizing errors between actual and evaluated states of the model. In order to investigate the efficiency of the API algorithm, numerical experiments are carried out on the piezoelectric chaotic resonator. The simulation results indicate that the API algorithm can be effective in identifying the unknown parameters for given chaotic systems with high accuracy and low deviations. Abstract :